PENGEMBANGAN INSTRUMEN PENILAIAN UNJUK KERJA BERBASIS IT PADA POKOK BAHASAN BERNYANYI SECARA VOKAL GRUP DI SMP - Eris Fahmi Rahmawan (Universitas PGRI Semarang, 2016)
This research was conducted using the research approach development (Research and Developmen) that steps are adapted from the spiral model. Instrument performance assessment (performance assessment) developed consisting of: (1) item task (task); (2) audio accompaniment; (3) an assessment rubric; (4) The observation sheet; and (5) guidelines for the interpretation of the results. Developing indicators of performance assessment instruments subject of vocal singing group performed with reference to the art of music learning curriculum seventh grade junior high school (SMP). Especially on basic competence (KD): (1) understanding of vocal technique vocal singing group; and (2) to sing songs in the vocal group. To assess the competence of the students in singing a vocal group used performance assessment techniques with engineering practice test assignment sing vocally area group. Based on the results of experiments performed at the stage of implementation of the model shows that, technically model of performance assessment on the subject of vocal singing group developed can be applied properly. Based on the analysis of reliability test performed using inter-class correlation coefficient analysis (intraclass correlation coefficients / ICC) type definition consistency and type of absolute agreement definition shows also that the assessment instruments developed have met the established criteria.Keywords: assessment, performance, singing, vocal group